OPTIMIZING ORGANIZATIONAL CULTURE IN FACING INDONESIAN CROSS-BORDER CRIME AND POST-REGIONAL PANDEMICS - Hilmy, Muhadzib Rezki (Polteknik Imigrasi, 2023)
Indonesian and regional cross-border crime trends have changed after the Covid-19 pandemic. The rapidly increasing mobility of people to restore the economy is a challenge to maintain national security. Immigration must work optimally, and this can be achieved if immigration has a good organizational culture. This discussion of organizational culture and cross-border crime uses qualitative library research. The results of this research show that the Directorate General of Immigration has implemented the dimensions of organizational culture according to Wilderom and Van den Berg, namely external orientation, department orientation and good development orientation. However, there needs to be an evaluation of the dimensions of job autonomy and orientation to human resources. It is hoped that this research can be a reference for the importance of good organizational culture so that an organization can optimally handle Indonesian and regional cross-border crime problems.